Artificial Intelligence and Humans: The Impact of AI on the Human Role in the Military - Hendriman Putra; Budi Eko Mulyono (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research explores the transformative impact of Artificial Intelligence (AI) on the human role in the military using a qualitative descriptive method. AI is increasingly automating tasks, enabling humans to focus on strategic and ethical decision-making. However, this shift necessitates adaptations in training, doctrine, and organizational structures. The research analyses the ethical challenges, including accountability and the prevention of unethical use, and highlights the critical importance of cybersecurity in mitigating risks. Key findings suggest that AI will significantly enhance operational efficiency while presenting new challenges related to human oversight, ethical considerations, and the need for robust cybersecurity measures. The study concludes with recommendations for developing training curricula, establishing ethical standards, and investing in cybersecurity to ensure the responsible and effective integration of AI in the military domain.